Nanomaterials–plants–microbes interaction: plant growth promotion and stress mitigation - Sodhi, Gurleen Kaur; Wijesekara, Tharuka; Kumawat, Kailash Chand; Adhikari, Priyanka; Joshi, Kuldeep; Singh, Smriti; Farda, Beatrice; Djebaili, Rihab; Sabbi, Enrico; Ramila, Fares; Sillu, Devendra; Santoyo, Gustavo; et al. (Frontiers in Microbiology, 2025)
Soil salinization, extreme climate conditions, and phytopathogens are abiotic and biotic stressors that remarkably reduce agricultural productivity. Recently, nanomaterials have gained attention as effective agents for agricultural applications to mitigate such stresses. This review aims to critically appraise the available literature on interactions involving nanomaterials, plants, and microorganisms. This review explores the role of nanomaterials in enhancing plant growth and mitigating biotic and abiotic stresses. These materials can be synthesized by microbes, plants, and algae, and they can be applied as fertilizers and stress amelioration agents. Nanomaterials facilitate nutrient uptake, improve water retention, and enhance the efficiency of active ingredient delivery. Nanomaterials strengthen plant antioxidant systems, regulate photosynthesis, and stabilize hormonal pathways. Concurrently, their antimicrobial and protective properties provide resilience against biotic stressors, including pathogens and pests, by promoting plant immune responses and optimizing microbial-plant symbiosis. The synergistic interactions of nanomaterials with beneficial microorganisms optimize plant growth under stress conditions. These materials also serve as carriers of nutrients, growth regulators, and pesticides, thus acting like “smart fertilizers. While nanotechnology offers great promise, addressing potential environmental and ecotoxicological risks associated with their use is necessary. This review outlines pathways for leveraging nanotechnology to achieve resilient, sustainable, and climate-smart agricultural systems by integrating molecular insights and practical applications.